Use of waste foundry sand (WFS) to produce protective coatings on aluminum alloy by plasma electrolytic oxidation - Souza, Carime dos Santos [UNESP]; Antunes, Maria Lúcia Pereira [UNESP]; Valentina, Luiz Veriano Oliveira Dalla; Rangel, Elidiane Cipriano [UNESP]; da Cruz, Nilson Cristino [UNESP] (Elsevier, 2019)
Exhaust dust is a solid byproduct resulting from the casting process. With the aim of finding an alternative use for this residue, evaluation was made of the possibility of producing ceramic coatings with the material. Coatings on 5052 aluminum alloys were obtained by the electrolytic plasma technique, using an electrolytic solution prepared with exhaust powder and distilled water (5 g/L). The electrolytic plasma was obtained by applying a potential difference of 650 V and frequency of 300 Hz, with deposition times of 300 and 600 s. Characterization of the residue was performed using X-ray fluorescence (XRF), scanning electron microscopy (SEM), energy dispersive spectroscopy (EDS), and X-ray diffraction (XRD). The coatings obtained were also characterized by SEM-EDS and XRD, and were analyzed to determine the contact angle, roughness, thickness, and mechanical wear. The coatings obtained with this residue, irrespective of the deposition time, were essentially composed of Al, Mg, Si, P, Ca, Fe, K, Ti, and Na, forming a ceramic material whose crystalline structure consisted mainly of alumina and quartz. The plasma electrolytic oxidation (PEO) coating obtained using a longer deposition time (600 s) presented a slightly different morphology and a crystalline structure in which the crystallized silicon was in the form of moissanite (SiC), resulting in improved mechanical properties of the coating. A longer deposition time led to increases in the number and size of the pores present in the coating. In addition, coalescence was observed at various points in the coating. It could be concluded that increases of the deposition time and the concentration of the electrolytic solution resulted in a higher contact angle, increased roughness, greater thickness, and less wear of the material.
Keywords: Aluminum alloy; Ceramic coating; Electrolytic plasma; Waste foundry sand